Velika Gospa pres de Bale (Istrie) : recherches archéologiques franco-croates a Bale. Vol. 1 - Jurković, Miljenko; Caillet, Jean-Pierre (Studies in Early Christian and Medieval art history and archaeology. Dissertationes et monographiae, 2007)
Sažetak